REVIEW OF POLYGRAPH INSTRUMENTS AS EVIDENCE IN COURT IN FULFILLING THE CRIMINAL PROCEDURE CODE JO LAW NUMBER 19 OF 2016 CONCERNING AMENDMENTS TO LAW NUMBER 11 OF 2008 CONCERNING ELECTRONIC INFORMATION AND TRANSACTIONS - Berti Nora Panjaitan; Chitto Chumbradika (Jurnal Scientia, 2023)
The polygraph instrument, a computed technology, has the ability to interpret deceit with up to 98% accuracy through physiological data management, such as blood pressure fluctuations, pulse frequency, respiratory frequency, and changes in skin moisture due to anxiety from the questions asked. The emergence of the Regulation of the Chief of Indonesian National Police (Perkap) Number 10 of 2009 Article 9 Section (2) Point A decided that the use of polygraph instruments as evidence in court would provide assistance to the Judge to decide verdicts during criminal cases. Dozens of criminal verdicts have been decided since 2009. Although it has been found that the result of the polygraph instrument hasn’t been used as evidence due to its scientific methods that don't meet the required objective elements, therefore it doesn’t have a place in the criminal code procedure (KUHAP). Implicit approvals could be found in Article 5 of the Bill of Act on Electronic Information and Transaction (UU ITE) Number 19 of 2016 on the amendment of UU ITE Number 11 of 2008; and Constitutional Court Decision (Putusan MK) Number 20/PUU-XIV/2016. In order to attain legal certainty over the role of the polygraph instrument in court, the author examined the issue by answering these two research questions: What is the urgency of using the polygraph instrument as evidence in court?; and How is the legal study of the use of the polygraph instrument as valid evidence in court as written in UU ITE Number 19 of 2016 on the amendment of UU ITE Number 11 of 2008. The purpose of this study, therefore, is to answer both of the research questions. Throughout this study, the author used judicial normative as its research method, while also using primary, secondary, and tertiary data. The primary data that were used during this research are KUHAP, UU ITE Number 19 of 2016 on the amendment of UU ITE Number 11 of 2008, other legislations and jurisprudence in relation to this study. The secondary data that were used during this research are scientific journals, articles, theses, and dissertations in relation to this study. The tertiary data that were used during this research are the English and Indonesian dictionaries. This study found that the polygraph instrument can be used as evidence in court through the Judge’s decision and based on the Judge’s convictions of the legislation, jurisprudence, as well as law and sense of justice that are developing in the society. In essence, the need for general, final, and binding law are crucial.